2021
DOI: 10.1093/cid/ciaa1382
|View full text |Cite
|
Sign up to set email alerts
|

The Limit of Detection Matters: The Case for Benchmarking Severe Acute Respiratory Syndrome Coronavirus 2 Testing

Abstract: Background Resolving the coronavirus disease 2019 (COVID-19) pandemic requires diagnostic testing to determine which individuals are infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The current gold standard is to perform reverse-transcription polymerase chain reaction (PCR) on nasopharyngeal samples. Best-in-class assays demonstrate a limit of detection (LoD) of approximately 100 copies of viral RNA per milliliter of transport media. However, LoDs of currently appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(88 citation statements)
references
References 13 publications
6
82
0
Order By: Relevance
“…16 Similar studies performed on samples with Ct >30 about 3-25% of the samples retested as negative depending on the kit used. [17][18][19] However, a recent study by Arnaut et al, highlights that the sensitivity of currently approved assay varies over 10,000fold and several low sensitivity (high LoD) assays will miss the majority of infected patients that could be easily identified by assays having high sensitivity (low LoD). 17 Further, a study by Winnet et al, identifies a case of pre-symptomatic household transmission from a healthy young adult to a sibling and a parent, with high Ct (low viral load) results in the early phase (pre-symptomatic) of the infection that could prevent transmission in the family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Similar studies performed on samples with Ct >30 about 3-25% of the samples retested as negative depending on the kit used. [17][18][19] However, a recent study by Arnaut et al, highlights that the sensitivity of currently approved assay varies over 10,000fold and several low sensitivity (high LoD) assays will miss the majority of infected patients that could be easily identified by assays having high sensitivity (low LoD). 17 Further, a study by Winnet et al, identifies a case of pre-symptomatic household transmission from a healthy young adult to a sibling and a parent, with high Ct (low viral load) results in the early phase (pre-symptomatic) of the infection that could prevent transmission in the family.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] However, a recent study by Arnaut et al, highlights that the sensitivity of currently approved assay varies over 10,000fold and several low sensitivity (high LoD) assays will miss the majority of infected patients that could be easily identified by assays having high sensitivity (low LoD). 17 Further, a study by Winnet et al, identifies a case of pre-symptomatic household transmission from a healthy young adult to a sibling and a parent, with high Ct (low viral load) results in the early phase (pre-symptomatic) of the infection that could prevent transmission in the family. 10 Furthermore, an analysis of serial RT-PCR assays and chest CT scans has demonstrated that the mean interval between the initial negative to positive RT-PCR results was 5.1 days ± 1.5, and the mean interval between initial positive to subsequent negative RT-PCR results was 6.9 days ± 2.3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, sputum samples show higher viral loads than throat swab samples, whereas low viral RNA is detected in urine or stool samples [ 75 ]. The two main factors that influence the quantitative measurement of viral roads are Cq values that are repeatable with acceptable uncertainty and a reliable means of converting from the Ct value to viral load [ 76 , 77 , 78 ]. For molecular diagnostic assays, a limit of detection (LoD) and a limit of quantification (LoQ) are also considered the lowest concentrations of target RNA that can be detected by RT-qPCR [ 79 ].…”
Section: Pcr-based Sars-cov-2 Detectionmentioning
confidence: 99%
“…However, there are conflicting reports as to which of several specimen types bear the highest viral load ( 1 3 ), and ultimately, the “preferred-specimen” specification was removed from interim CDC guidance on 29 April 2020 ( 4 ). Sensitivity is a complex issue, however, as detection in the upper airways (nasopharynx and oropharynx) is affected by multiple factors, including duration of illness prior to testing ( 5 ) and the limit of detection (LoD) of the reverse transcription (RT)-PCR assay used ( 6 ).…”
Section: Introductionmentioning
confidence: 99%